2010
DOI: 10.1016/j.pain.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Functional abdominal pain in childhood and adolescence increases risk for chronic pain in adulthood

Abstract: A few studies of long-term outcomes for pediatric functional abdominal pain (FAP) have assessed acute non-abdominal pain at follow-up, but none has assessed chronic pain. We followed a cohort of pediatric patients with FAP (n = 155) and a well control group (n = 45) prospectively for up to 15 years. Participants ranged in age from 18 to 32 years at a follow-up telephone interview. FAP patients were classified as Resolved (n = 101) versus Unresolved (n = 54) at follow-up, based on whether they reported symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(142 citation statements)
references
References 33 publications
1
137
0
3
Order By: Relevance
“…Participants were recruited from a sample participating in a large prospective study of adolescents and young adults with childhood functional abdominal pain [25][26][27]. Participants from the original study had presented to the Vanderbilt Pediatric Gastroenterology Clinic for evaluation of chronic abdominal pain when they were 8-16 years old.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited from a sample participating in a large prospective study of adolescents and young adults with childhood functional abdominal pain [25][26][27]. Participants from the original study had presented to the Vanderbilt Pediatric Gastroenterology Clinic for evaluation of chronic abdominal pain when they were 8-16 years old.…”
Section: Samplementioning
confidence: 99%
“…To address this gap in the literature and build upon our prior work [25][26][27], in this study, we examined the effect of resolution of chronic pain on BP-related hypoalgesic mechanisms as they relate to responses to both static and dynamic evoked pain stimuli. Specifically, we compared young adults with a known childhood history of functional abdominal pain in whom the condition had resolved versus not resolved at the time of testing, regarding the associations between resting BP and thermal pain threshold, tolerance, and temporal summation.…”
Section: Introductionmentioning
confidence: 99%
“…Taigi nepakankamai sprendžiant lėtinio skausmo problemas vaikystėje ar paauglystėje, didėja rizika šiems ligoniams ir ateityje turėti funkcinę negalią bei psichologinių problemų [30]. Be to, ilgalaikiai tyrimai pateikia įtikina-mų įrodymų, kad negydomas skausmas, patirtas vaikystė-je, dažnai tęsiasi ir pasireiškia naujomis skausmo formomis suaugus [31].…”
Section: Lėtinio Skausmo Sukeltos Socialinės Problemosunclassified
“…Another study which prospectively followed youth with FAP for up to 15 years found that they may be at increased risk for chronic pain and headache [50]. The most long lasting benefit among the different treatments for childhood FGID seems to be the gut-directed hypnotherapy.…”
Section: Natural Historymentioning
confidence: 99%